Technostress Among Graduate Students in the Post-COVID-19 Era - Singh, Rajesh (Journal of Educational Research and Policies, 2025)
The COVID-19 pandemic has significantly transformed the educational landscape, forcing graduate students to rapidly adapt to online learning. This transition has led to the emergence of technostress—stress caused by excessive use of technology. Graduate students, already burdened by academic and research responsibilities, face challenges such as digital platform overload, virtual communication fatigue, information overload, time management difficulties, and increased performance pressure. The consequences of technostress include mental health issues, reduced productivity, and physical health problems. This article explores the causes and consequences of technostress in graduate students and discusses potential strategies to mitigate its impact in the post-COVID era.